2000
DOI: 10.1038/sj.bdj.4800480
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment for people with challenging behaviour: general anaesthesia or sedation?

Abstract: The dental care of people with severe learning disability and challenging behaviour presents many problems. The maintenance of oral health by regular examination, prevention and treatment may be difficult because of the limitations in patient cooperation. In many cases the diagnosis of orofacial pain may need to be discounted as a cause of uncharacteristic and sometimes aggressive behaviour. In such cases the use of general anaesthesia for examination and treatment would seem to be the obvious option but this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…It may also help to increase regular access to routine care, thus avoiding the repercussions of neglect on general health and quality of life in this population. 1 The use of a safe, simplified sedation technique, with a single agent, may be an argument for extending the indications of conscious sedation to other simple acts performed in the institutionalized setting by qualified care staff, such as phlebotomy or wound dressing. 17 It is essential, however, that anaesthetists be involved in the development, standardization, and teaching of such techniques and that mandatory qualifications be put in place around the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also help to increase regular access to routine care, thus avoiding the repercussions of neglect on general health and quality of life in this population. 1 The use of a safe, simplified sedation technique, with a single agent, may be an argument for extending the indications of conscious sedation to other simple acts performed in the institutionalized setting by qualified care staff, such as phlebotomy or wound dressing. 17 It is essential, however, that anaesthetists be involved in the development, standardization, and teaching of such techniques and that mandatory qualifications be put in place around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Conscious sedation may provide an alternative management method, but these techniques have traditionally been contraindicated for persons with intellectual disability or a psychiatric disorder for fear of aggravating existing behavioural or medical problems, or because of perceived lack of cooperation. [1][2][3][4][5] The effects of inhalation sedation using nitrous oxide in oxygen (N 2 O/O 2 ) are mild, of rapid onset, reversible, short-lasting, and of little systemic impact compared with other sedative drugs. 6 Indeed, the American Society of Anesthesiologists Task Force on sedation and analgesia by non-anaesthetists considers that inhalation of less than 50% N 2 O entails minimal risks and, thus, excluded this mode of anxiolysis from their practice guidelines.…”
mentioning
confidence: 99%
“…6 The use of propofol as an intravenous induction agent is very useful, having been associated with fast clearance and reducing postoperative nausea and vomiting. 7 All the above mentioned advancements have significantly improved the safety of anesthetic technique, a reduction in adverse events, and has resulted in increased patient satisfaction with DGA in an office-based ambulatory setting.…”
Section: Dental Treatment Under General Anesthesia In Healthy and Medmentioning
confidence: 99%
“…4 Besides, it has been reported that DGA is used as multidisciplinary approach for oral rehabilitations under DGA that involve personnel with different dental specialities which increase the procedure cost. [4][5][6] The availability of rapid and short-acting anesthetics such as sevoflurane and propofol has improved the general anesthesia (GA) technique and facilitated the early recovery of…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] As an alternative to this radical and limited approach, the use of intravenous sedation provided in primary care as an operator sedation ist has been shown to be an effective management strategy for people with disability. 5,6 The specific technique of using oral or intranasal midazolam to allow cannulation followed by intrave nous sedation of the same drug has made available the option for comprehensive care. This would include effective rou tine examinations, periodontal care, and restorative treatment.…”
Section: Introductionmentioning
confidence: 99%